(untitled) (Indian Journal of Arid Horticulture, 2025)
The adoption of IPM approaches in ber resulted in a lower incidence of fruit damage, with a 65% mean reduction compared to farmer’s practices. Mean higher yield of 111.2 q/ ha was recorded in the demonstration compared to 77.84 q/ ha in farmer’s practice, representing a 42.86% increase. This has resulted in higher mean net returns of Rs. 1,79,640/- ha with a Benefit Cost Ratio (BCR) of 3.76 in the demonstration, compared to Rs. 1,08,248/- ha in farmer’s practice with a BCR of 2.72. The current study’s findings clearly indicated that using IPM technology against the ber fruit fly was more effective and economical than conventional methods.